POLLUTION OF PESTICIDE RESIDUES IN RIVERS : REVIEW - Desy Aryani; Sri Wahyuningsih (Jurusan Perikanan dan Kelautan, 2021)
Pesticides has been widely used in pest eradiction in agriculture sector. The types of pesticides are used to kill grass (herbicides), fungi and bacteria (fungicides), and insects (insecticides). In general, those pesticides are contain toxic compounds, such as dichlorodiphenyl trichlorethane (DDT), dieldrin, and polychlorobiphenyls (PCB) which are lipophilic, persistent, and difficult to degrade. In general, fresh waters such as rivers are more at risk of pollution due to pesticide residues that enter through runoff. The pesticides residues of the nearby rivers can easily affect the water quality, sediment as well as causing toxic effects on non-target organisms through the food chain. The method in this paper refers to several research results that have been carried out, by providing an overview of pesticide residue pollution in rivers. The results showed that pesticide residues mostly contaminated rivers in China, with DDT and hexachloro cyclohexane (HCH) being the most commonly found and studied species. Several rivers in China have concentrations of DDT and HCH beyond the highest concentration levels in both water, sediments and aquatic organisms.Keywords : Pesticide, Pollution, River